La persuasió de la lògica i la lògica de la persuasió: les proposicions en vers del Dictat de Ramon (1299) de Ramon Llull. - FERNÀNDEZ-CLOT, ANNA; TOUS, FRANCESC (Scripta)
In this paper, we deal with the study of the Dictat de Ramon, a work in verse that has the aim to provide arguments proving the most important articles of Christian religion. Each one of the six parts in which the poem is divided contains twenty, ten or twelve couplets that condense the arguments into the form of a proposition or maxim. Firstly, we analyze the semantic and logcial structures of the propositions, among which stand out the conditional clauses; secondly, we examine the function of the rhyme and the versification, and we sum up the stylistic and rhetorical figures used to compose the couplets; finally, we evaluate the reception of the text. One important aim of our study is to emphasize that the choice of verse and maxims is clearly linked with the addresee of the text, the king James II of Aragon, and with the petition that concludes the poem: the request of a permission to preach in the sinagogues and the mosques of the territories of the Kingdom of Aragon.